2017
DOI: 10.1021/acs.biochem.7b01029
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Ferrous Ion Binding to Retinal Guanylate Cyclase Activator Protein 5 from Zebrafish Photoreceptors

Abstract: Sensory guanylate cyclases (zGCs) in zebrafish photoreceptors are regulated by a family of guanylate cyclase activator proteins (called GCAP1-7). GCAP5 contains two non-conserved cysteine residues (Cys15 and Cys17) that could in principle bind to biologically active transition state metal ions (Zn2+ and Fe2+). Here, we present nuclear magnetic resonance (NMR) and isothermal titration calorimetry (ITC) binding analysis that demonstrate the binding of one Fe2+ ion to two GCAP5 molecules (in a 1:2 complex) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 44 publications
4
41
0
1
Order By: Relevance
“…The amino acid sequence of the zebrafish homolog called GCAP5 is the most divergent compared to the amino acid sequences of mammalian GCAP1 and GCAP2 (Figure 1 ). Two non-conserved Cys residues in GCAP5 (Cys 15 and Cys17) were shown recently to ligate Fe 2+ (Lim et al, 2017 ). Fe 2+ -binding to GCAP5 serves as a potent inhibitor and the Fe 2+ -bound GCAP5 is unable to activate RetGC at low Ca 2+ levels in light-adapted photoreceptors, suggesting that Fe 2+ binding to GCAP5 may serve as a redox sensor for phototransduction in zebrafish photoreceptors (Lim et al, 2017 ).…”
Section: Ncs Proteins Have Distinct Dimeric Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The amino acid sequence of the zebrafish homolog called GCAP5 is the most divergent compared to the amino acid sequences of mammalian GCAP1 and GCAP2 (Figure 1 ). Two non-conserved Cys residues in GCAP5 (Cys 15 and Cys17) were shown recently to ligate Fe 2+ (Lim et al, 2017 ). Fe 2+ -binding to GCAP5 serves as a potent inhibitor and the Fe 2+ -bound GCAP5 is unable to activate RetGC at low Ca 2+ levels in light-adapted photoreceptors, suggesting that Fe 2+ binding to GCAP5 may serve as a redox sensor for phototransduction in zebrafish photoreceptors (Lim et al, 2017 ).…”
Section: Ncs Proteins Have Distinct Dimeric Structuresmentioning
confidence: 99%
“…Two non-conserved Cys residues in GCAP5 (Cys 15 and Cys17) were shown recently to ligate Fe 2+ (Lim et al, 2017 ). Fe 2+ -binding to GCAP5 serves as a potent inhibitor and the Fe 2+ -bound GCAP5 is unable to activate RetGC at low Ca 2+ levels in light-adapted photoreceptors, suggesting that Fe 2+ binding to GCAP5 may serve as a redox sensor for phototransduction in zebrafish photoreceptors (Lim et al, 2017 ). Structurally, the Fe 2+ binding by Cys15 and Cys17 bridges two GCAP5 molecules into a [Fe(SCys) 4 ] dimeric complex (Lim et al, 2017 ) like that observed previously in two-iron superoxide reductases (deMaré et al, 1996 ; Min et al, 2001 ; Emerson et al, 2003 ).…”
Section: Ncs Proteins Have Distinct Dimeric Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The variety of zRec isoforms is reminiscent of zebrafish GCAPs, of which six isoforms are expressed in the zebrafish retina ( Imanishi et al, 2004 ; Rätscho et al, 2009 ). Detailed studies on zGCAP expression profiles in larval and adult animals, their regulatory properties, Ca 2+ sensitivities, and conformational dynamics revealed a differential action mode for each protein supporting a Ca 2+ relay mode of Ca 2+ -dependent negative feedback regulation ( Scholten and Koch, 2011 ; Fries et al, 2012 ; Sulmann et al, 2015 ; Lim et al, 2017 ). We suggest a similar regulatory mode for zRec forms.…”
Section: Introductionmentioning
confidence: 94%